What role does transactional sex play in the HIV/STI and reproductive health risk behaviour among high-tier entertainment centre workers in China? - Mantell, Joanne E. (Glob Public Health, 2015)
China’s rapid economic growth over the last three decades has led to increased population wealth and the proliferation of entertainment centres where people can conduct business, relax and meet new people. Little is known about the sexual risk behaviours of employees at high-tier entertainment centres. This paper addresses this gap in knowledge by comparing HIV risk perception and sexual and reproductive health behaviours among female and male employees at three high-tier entertainment centres in two cities in China, comparing those who report a history of transactional sex to those who do not. In both cities, participants who reported a history of transactional sex were more likely than those without a history of transactional sex to report multiple sexual partnerships, more lifetime sexual partners, a history of STIs, having anal sex and/or recent abortions, and were more likely to perceive themselves to be at risk for STIs/HIV. However, risk behaviour was also high among those with no history of transactional sex. These findings highlight the need for targeted sexual and reproductive health initiatives for employees in these work settings.